2021
DOI: 10.11336/jjcrs.12.27
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of maximal muscle contraction force induced by high-frequency magnetic stimulation: a preliminary study on the identification of the optimal stimulation site

Abstract: Purpose: To identify the optimal stimulation site and technique for inducing strong muscle contraction using a high-frequency magnetic stimulator. Methods: High-frequency magnetic stimulation was administered to the right vastus lateralis (VL) of eight healthy adults at maximal intensity within the range of tolerable pain. The stimulation sites were as follows: section A, the area between the lateral edge of the base of the patella (LEBP) and the distal one-third of the thigh (point D); section B, the area bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The right vastus lateralis (VL) was magnetically stimulated according to previous reports [17,[20][21][22][23]. Participants were seated with their right knee and hip joints flexed at 75°.…”
Section: Stimulation Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The right vastus lateralis (VL) was magnetically stimulated according to previous reports [17,[20][21][22][23]. Participants were seated with their right knee and hip joints flexed at 75°.…”
Section: Stimulation Conditionsmentioning
confidence: 99%
“…Thus, rPMS intervention studies have inconsistent results and are limited in number compared with studies on electrical stimulation. We have previously examined the stimulation methods, such the intensity and application site, and confirmed that strong muscle contraction can be obtained by selecting the optimal stimulation intensity and application site [ 16 , 17 ]. Differences in the shape of the stimulating coil can have a large effect on muscle contraction.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that when the type of the coil is the same, the larger the coil size, the stronger the muscle contraction force is induced 13 . In the studies related to stimulation methods, it has been confirmed that strong muscle contraction could be obtained by correctly selecting the stimulation intensity and site 11,14 . Consequently, the effects of the type of equipment and stimulation method on the degree of muscle contraction have been clarified.…”
mentioning
confidence: 94%
“…13 In the studies related to stimulation methods, it has been confirmed that strong muscle contraction could be obtained by correctly selecting the stimulation intensity and site. 11,14 Consequently, the effects of the type of equipment and stimulation method on the degree of muscle contraction have been clarified. However, the analysis of factors related to participant characteristics is still insufficient, and it has only been reported that muscle contraction induced by magnetic stimulation was weak in healthy participants with thicker subcutaneous fat.…”
mentioning
confidence: 99%
“…However, recently, a device with a small coil for stimulating the suprahyoid muscle has been developed and applied. It has the potential to replace NMES, which has been considered as a therapeutic stimulation modality to improve reduced hyoid elevation [16].…”
Section: Introductionmentioning
confidence: 99%